علاقة مستوى الطموح بالنضج المهني لدى طلبة الثالثة ثانوي - بالمسعود، آمال (جامعة الوادي university of Eloued, 2020)
الملخص: تهدف هذه الدراسة إلى التعرف على مدى ارتباط مستوى الطموح بالنضج المهني على عينة من طلاب السنة الثالثة ثانوي, من خلال الإجابة على الإشكال التالي: هل توجد علاقة ذات دلالة إحصائية بين مستوى الطموح والنضج المهني لدى طلاب الثالثة ثانوي ببلدية بمتقن كركوبية خليفة بالرباح , حيث تم إتباع المنهج الوصفي ألارتباطي للتحقق من فرضيات الدراسة , باستخدام مقياسي مستوى الطموح والنضج المهني لجمع البيانات وتم تطبيقهما على عينة تكونت من 30 طالب وطالبة من متقن كركوبي خلية بالرباح , ومن خلال اختيار الفرضيات باستخدام معامل الارتباط سبيرمان قد توصلت الدراسة إلى أنه : - لا توجد علاقة ذات دلالة إحصائية بين مستوى الطموح والنضج المهني. - لا توجد علاقة ذات دلالة إحصائية بين مستوى الطموح والتأكد في النضج المهني. - لا توجد علاقة ذات دلالة إحصائية بين مستوى الطموح والاهتمام في النضج المهني. - لا توجد علاقة ذات دلالة إحصائية بين مستوى الطموح والاستقلال في النضج المهني. - توجد علاقة ذات دلالة إحصائية بين مستوى الطموح وتوفر المعلومات في النضج المهني. - لا توجد علاقة ذات دلالة إحصائية بين مستوى الطموح والتوفيق في النضج المهني. Résumé : The aim of this study is to identify to which extent ambition's level is related to professional maturity on a sample of third-year high school students, and this by answering the following problem: Is there a statistically significant relationship between ambition's level and professional maturity among third-school students of Kerkoubia technical school? where the descriptive correlational approach was used to verify the study hypotheses using two measures of ambition's level and professional maturity to collect the data. They were applied to a sample consisting of 30 male and female students from Kerkoubia technical school in Robbah, and by selecting the hypotheses using the Spearman correlation coefficient. The study concluded that : - There is no statistically significant relationship between ambition's level and professional maturity. - There is no statistically significant relationship between ambition's level and the certainty in professional maturity. - There is no statistically significant relationship between ambition's level and interest in professional maturity. - There is no statistically significant relationship between ambition's level and independence in professional maturity. - There is a statistically significant relationship between ambition's level and the availability of information in the professional maturity. - There is no statistically significant relationship between ambition's level and success in professional maturity.
دراسة ميدانية وصفية ارتباطيه على عينة من طلبة مرحلة التعليم الثانوي بمتقن كركوكبية خليفة بالرباح
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: مستوى الطموح، النضج المهني; Niveau ambitieux, maturité professionnelle; Ambitious level, professional maturity